Comparison of Polylactic Acid Polycondensation Using LASC Fe(DS)3 Catalyst and FeCl3 Metal Catalyst - Saputra, Bayu Yusuf Eka; Aziz, Ahmad Musonnifin; Rohmah, Aisyah Alifatul Zahidah; Ni'mah, Hikmatun; Widjaja, Tri (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
Polylactic acid (PLA), also known as lactic acid, has become a promising candidate as a renewable resource for plastic production. The use of PLA as a plastic material can significantly reduce the problems caused by waste. In the production of Polylactic acid (PLA), there are byproducts such as water, while metal Lewis such as Fe (III) used in PLA production can rapidly decompose and be deactivated by water. This research aims to synthesize a water-resistant Lewis catalyst by Fe (III) Lewis metals with a surfactant called Sodium dodecyl sulfate (SDS), which will bond together to form Fe (III) dodecyl sulfate [Fe(DS)3]. This catalyst will then be compared to FeCl3 metal catalysts in terms of performance in PLA synthesize using the polycondensation method. The water-resistant Lewis catalyst is characterized using Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD), and Thermogravimetric Analysis (TGA). As for the PLA synthesized with Fe(DS)3 and FeCl3 catalysts under the same operating conditions, it is analyzed using viscometry to determine its molecular weight, Fourier Transform Infrared (FTIR), and X-Ray Diffraction (XRD). The results of the analysis of the LASC catalyst include: 1) FTIR spectra of Fe(DS)3 and SDS show similarity in stretching and bending vibration bands. 2) Crystallinity indices of 36.81% and 15.82% are obtained for SDS and Fe(DS)3, respectively. Results of the PLA analysis include: 1) The optimum temperature is 180 ℃, as it leads to an increase in molecular weight, while at 200 ℃, degradation occurs, resulting in a decrease in molecular weight. 2). FTIR result shows that lactic acid polymerization was achieved. 3) XRD analysis shows gentle diffraction from 10° to 26° which similar with literature. 4) The yields of PLA molecules synthesized by Fe(DS)3 gain with higher molecular weight compared to FeCl3 catalyst.